Klasifikasi Sistem Pola Agroforestry Kawasan Hutan Kemasyarakatan Desa Gantarang Kabupaten Sinjai - arham, Arham (Program Studi Kehutanan Fakultas Pertanian Universitas Islam Makassar, 2025)
Agroforestry represents a sustainable land management approach combining forestry andagricultural components to enhance rural livelihoods. This study examined agroforestry patternsimplemented by the Lestari Forest Farmer Group in Gantarang Village, Sinjai Regency, SouthSulawesi. Using descriptive qualitative methodology, data were collected through structuredinterviews and field observations involving 50 farmer respondents. Results revealed four distinctagroforestry systems: agrisilviculture dominated at 82%, followed by agrosilvopasture (12%),agrosilvofishery (4%), and silvopasture (2%). Three spatial arrangements were identified: randommixture (88%), tree along border (8%), and alternate rows (4%). Dominant forestry species includedteak (Tectona grandis), mahogany (Swietenia mahagoni), and nutmeg (Myristica fragrans), whileagricultural crops comprised cassava and pepper. Most farmers (88%) managed 0.5-1 hectare plotswith 2-3 years experience. Male participation predominated (88%) with basic education levels (64%primary school). The random mixture pattern prevailed due to traditional practices and economicdiversification benefits. Agrisilviculture's dominance reflected farmers' preference for familiaragricultural practices over complex integrated systems. Key challenges included limited technicalknowledge, capital constraints, and market access issues. The study demonstrates agroforestry'spotential for sustainable land use and income diversification, though targeted extension servicesand capacity building remain essential for optimal implementation and long-term sustainability.